Perilipin 2 Impacts Acute Kidney Injury via Regulation of PPARα. (9th September 2021) - Xu, Sujuan; Lee, Edward; Sun, Zhaoxing; Wang, Xiaoyan; Ren, Ting; Zou, Zhouping; Jin, Jifu; Li, Jie; Zhang, Jian; Li, Yingxiang; Yang, Qiang; Zhang, Yang; et al.
Abstract : Renal ischemia-reperfusion (I/R) can induce oxidative stress and injury via the generation of reactive oxygen species (ROS). Renal proximal tubular cells are susceptible to oxidative stress, and the dysregulation of renal proximal tubular cellular homeostasis can damage cells via apoptotic pathways. A recent study showed that the generation of ROS can increase perilipin 2 (Plin2) expression in HepG2 cells. Some evidence has also demonstrated the association between Plin2 expression and renal tumors. However, the underlying mechanism of Plin2 in I/R-induced acute kidney injury (AKI) remains elusive. Here, using a mouse model of I/R-induced AKI, we found that ROS generation was increased and the expression of Plin2 was significantly upregulated. An in vitro study further revealed that the expression of Plin2, and the generation of ROS were significantly upregulated in primary tubular cells treated with hydrogen peroxide. Accordingly, Plin2 knockdown decreased apoptosis in renal proximal tubular epithelial cells treated with hydrogen peroxide, which depended on the activation of peroxisome proliferator-activated receptor α (PPAR α ). Overall, the present study demonstrated that Plin2 is involved in AKI; knockdown of this marker might limit apoptosis via the activation of PPAR α . Consequently, the downregulation of Plin2 could be a novel therapeutic strategy for AKI.